Moderate to vigorous physical activity, not sedentary time, is associated with total and regional adiposity in a sample of UK adults at risk of type 2 diabetes. (21st September 2016) - Harrington, D M; Edwardson, C L; Henson, J; Khunti, K; Yates, T; Davies, M J
Abstract: How sedentary time (ST) relates to total and regional adiposity and whether these associations are independent of moderate- to vigorous-intensity physical activity (MVPA) are of clinical and public health interest. We assessed the relationship between objectively measured MVPA, ST and ST breaks in adults at risk of type 2 diabetes. The sample consisted of 163 adults (37–75 years) recruited from primary care. Dual energy x-ray absorptiometry (iDXA, GE Corp) was used to estimate total and regional (appendages and trunk) fat mass as well as fat mass in the abdominal (android) and hip/thigh (gynoid) regions. The Actigraph GT3X was worn for 7 days (participants with  ⩾4 valid days included herein) and published cut-points were applied to 15 s epoch data to estimate mean MVPA, ST and breaks in ST. Multiple regression investigated associations between both ST and MVPA with total and regional adiposity without and with adjustment for known and potential confounders (including total lean mass) and for each other. MVPA was negatively and significantly associated with total ( b   =  −62; p   =  0.002), and regional ( p   <  0.05) adiposity before and after adjusting for confounders including ST. Although ST was positively and significantly associated with total ( b   =  46.4; p   =  0.002) and regional adiposity (all p   ⩽  0.007), these relationships disappeared after adjustment for MVPA ( p   >  0.05). Sedentary breaks were not significantly related to adiposity before or after adjustment. An age-by-MVPA interaction for total, android, gynoid and trunk fat revealed that MVPA did not remain significant when controlling for ST and other covariates in the adults over 65 years old. In this sample of adults at risk of type 2 diabetes, MVPA, and not ST, was associated with total and regional adiposity after adjustment for each other. However, in older adults at risk of T2D weight related benefits may be gained from reducing daily ST and increasing MVPA.